Enhancing India-Pakistan economic cooperation: Prospects for Indian investment in Pakistan - Palakh Jain; Samridhi Bimal (Indian Council for Research on International Economic Relations (ICRIER), 2014)
With the growing importance of FDI among developing countries, a number of research studies have been conducted for capturing the bilateral investment regime across countries. However, the potential of investment between the two important nations of South Asia, namely, India and Pakistan, remains unexplored. Against the background of investment trends, the attractiveness of Pakistan as a host destination, and the growing importance of India as a source destination for foreign investment in South Asia, there is great potential for Pakistan to attract FDI from India. In this context, the paper identifies sectors in Pakistan that hold potential for investment. While the removal of restrictions on FDI flows has opened up new opportunities, much remains to be done on both sides to facilitate and enhance investment flows. To realize the untapped investment potential, the two countries would have to undertake several measures in several areas. In this context, this paper examines the regulatory regime governing investment flows between the two countries and the barriers to investment in Pakistan in order to bring out the need for policy coherence in investment with other areas of investment facilitation and business practices. Both governments need to address the regulatory and administrative challenges Pakistan faces in attracting investment from India. Innovative solutions are needed to increase investment flows. The paper proposes stage-wise recommendations for better and sustained formulation of investment relations between India and Pakistan. Enhanced investment flows will not only benefit the two countries economically, but will also serve as a powerful tool to build peaceful bilateral relations.
Keywords: F210; F230; 330; Outward FDI; India; Pakistan; opportunities; barriers; political stability; sectors; policy recommendations